(3dH GddHGH aj JMQjQ GdCfSGHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GHf GdGKjQ , YR GdOjf CHh GdMSf,J (B630 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdoeJfRg Yf GdCSHGg h GdCfSGH s
(3BNQgG (B:s
(3hbO GSJbjJ aj gPG GdoeNJUQ cKjQoG eeG aGJgeG hGSJOQcJ efg LeoYkG LekG, hZGdH eGROJg ef oeYLe GdoHdOGf djGbhJ GdMehj QMeI Gdg JYGdi Ydjge CLeYjf s
(3GfXQ Qbe (B1190 (3JGQjNs
(3fSNI KGfjIs
(3ofbdJ ef CUd ofbd ef CUd GdeoDda ceG hQO HBNQ GdfSNIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs